2018
DOI: 10.1002/chem.201802547
|View full text |Cite
|
Sign up to set email alerts
|

The Important Role of the Nuclearity, Rigidity, and Solubility of Phosphane Ligands in the Biological Activity of Gold(I) Complexes

Abstract: A series of 4-ethynylaniline gold(I) complexes containing monophosphane (1,3,5-triaza-7-phosphaadamantane (pta; 2), 3,7-diacetyl-1,3,7-triaza-5-phosphabicyclo[3.3.1]nonane (3), and PR , with R=naphthyl (4), phenyl (5), and ethyl (6)) and diphosphane (bis(diphenylphosphino)acetylene (dppa; 7), trans-1,2-bis(diphenylphosphino)ethene (dppet; 8), 1,2-bis(diphenylphosphino)ethane (dppe; 9), and 1,3-bis(diphenylphosphino)propane (dppp; 10)) ligands have been synthesized and their efficiency against tumor cells evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 99 publications
5
44
0
Order By: Relevance
“…Hydrogen atoms at positions 1, 2, and 4 (see position numbering in Scheme 2) are more affected by the coordination of the metal atom with a 0.1 ppm downfield shift. The 31 P{ 1 H} NMR spectra show in all cases one signal, as a direct indication of the formation of only one product, that is approximately 50–60 ppm downfield shifted with respect to the free phosphane, as previously observed in other similar reactions (Figures S3–S22 in the Supporting Information) [24, 26–31] …”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Hydrogen atoms at positions 1, 2, and 4 (see position numbering in Scheme 2) are more affected by the coordination of the metal atom with a 0.1 ppm downfield shift. The 31 P{ 1 H} NMR spectra show in all cases one signal, as a direct indication of the formation of only one product, that is approximately 50–60 ppm downfield shifted with respect to the free phosphane, as previously observed in other similar reactions (Figures S3–S22 in the Supporting Information) [24, 26–31] …”
Section: Resultssupporting
confidence: 78%
“…The Au−C and C≡C distances and P‐Au‐C and Au‐C≡C angles (Table 1) are in the usual ranges for Au I alkynyl complexes [28, 31–41] . Linear coordination of the phenanthrene ligands at the Au I centers is observed, with P‐Au‐C angles of 172.6–179.0°.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Previous work reported by 4 us has been mainly based on linear mononuclear compounds containing aromatic chromophores that can improve the self-assembly process by the presence of    interactions. 3,5,11,12,29 In this work, we can demonstrate that the absence of this type of interactions, based on the presence of aromatic chromophores, does not prevent intermolecular contacts and aggregation leading to the formation of very long fibers. The simplicity of the present molecules are particularly important since it can be demonstrated that only Au(I) and probably some hydrogen bonds coming from phosphine units are necessary in these supramolecular assemblies.…”
Section: Introductionmentioning
confidence: 76%
“…They obtained these compounds after synthetizing Li2C2 (Na2C2) by reacting the elemental Li (Na) with acetylene gas. New materials with distinct structures and different properties have been updated by Głodek et al [14], Chan et al [15], Svahn et al [16], Marmol et al [17], and Sanchez-de-Diego et al [18], using multiple diagnostic techniques. On the other hand, there are many fields of use of these structures in several areas, as shown by Lankelma et al [19], Tian et al [20], Kuroda et al [21], Hau et al [22], and Zhou et al [23].…”
Section: Introductionmentioning
confidence: 99%